2023
DOI: 10.1038/s41598-023-36691-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, sources, and risk assessment of PAHs in borehole water from the vicinity of an unlined dumpsite in Awka, Nigeria

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are contaminants of interest in the ecosystem due to associated health risks. Therefore, their detection in the environment is important. In this regard, the risk assessment of PAHs in borehole water near the unlined dumpsite in Anambra State was investigated. Samples of borehole water (16 each) were collected from the study and control areas during both seasons. The PAH concentrations in the borehole water samples were analyzed using gas chromatography. The mean PAH con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…A surge in environmental pollution has accompanied the rapid expansion of urbanization and industrialization 23 . Earlier studies have reported that heavy metal concentrations, particularly for elements such as Hg and Co, were elevated in the groundwater of urban areas compared to non-urbanized regions within the Pearl River Delta 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A surge in environmental pollution has accompanied the rapid expansion of urbanization and industrialization 23 . Earlier studies have reported that heavy metal concentrations, particularly for elements such as Hg and Co, were elevated in the groundwater of urban areas compared to non-urbanized regions within the Pearl River Delta 24 .…”
Section: Discussionmentioning
confidence: 99%
“…The specific activity of G6PD obtained in our study was measured at 0.83 U/mg protein, and difference from previous reports 17 , 29 . The variations in specific activities of G6PD could be attributed to the enzyme's different sources and origins 23 . Likewise, the G6PD exhibited a molecular weight of 68.89 kDa, which may have two maximum activity values according to the LOWSS linear regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…On the environmental level, contamination of surface and underground water occurs via landfill leaching, petroleum spills, fossil fuel combustion, and improper disposal of industrial wastes [ 12 ]. Surface water is more vulnerable to PAH contamination than underground, rendering the consumption of surface water due to a lack of safety.…”
Section: Introductionmentioning
confidence: 99%